KEHIDUPAN PEREMPUAN YANG DIGAMBARKAN DALAM KARYA WALKER DAN TOHARI: STUDI PERBANDINGAN - Rorintulus, Olga A.; Wuntu, Ceisy N.; Tatipang, Devilito Prasetyo; Lolowang, Imelda; Merlin M. Maukar (UIN Alauddin Makassar, 2022)
This research raises the deconstruction of patriarchal power over women, social, race and education in the novels. The researcher examines this matter with the aims of uncovering and describing gender issues in this study based on the existence of women who feel oppressed trying to fight for their rights. In this study, the researcher compares the same situation between the two main characters in these two novels which is described using a qualitative descriptive method. The data sources in this research are the novels Bekisar Merah and The Color Purple. The data were obtained by reading, taking notes, and coded each sentence related to the research data. In analyzing the data, the researcher uses the Feminist Intersectional theory to examine in depth the oppression of women from all aspects. The results of this study indicate that there is discrimination experienced by the two main characters in the novel, discrimination in terms of gender, family, society, race and education. Marginalization is also felt by these two characters due to differences in Gender, Race, and Family backgrounds that give rise to marginalization, the existence of dominance from the other party towards one of the sexes can be marginalized, in addition, the injustice has to do with the subordination, stereotypes, and violence experienced by the female characters in the novel. However, the form of gender equality in this case is the need for mutual respect between men and women, women as equal partners of men are more precisely as mentors and equal partners.